A STUDY TO ASSESS THE PREDICTION OF PERINEAL TRAUMA DURING CHILD BIRTH USING STRIAE GRAVIDARUM AMONG THE POST NATAL MOTHERS AT SELECTED HOSPITALS, SASARAM, ROHTAS, BIHAR - K, Latha; Kumar, Gaurav; Kumari, Soni; Vardhan, Harsh; Priya, Vishnu; Kumari, Anjali; Malik, Irfan (International Journal of Pharma and Bio Sciences, 2026)
Perineal trauma during childbirth poses significant maternal health concerns, resulting in both immediate and long-term complications such as pain, infection, incontinence, and psychological distress. This study aimed to evaluate the relationship between the severity of striae gravidarum and perineal trauma during vaginal delivery, as well as to explore associated demographic and obstetric factors. Conducted at Narayan Medical College & Hospital and Sadar Hospital, Sasaram, Bihar, the research employed a quantitative, non-experimental, descriptive correlational design involving 60 postnatal mothers selected through convenience sampling. Data collection tools included a demographic proforma, the Atwal Scale for striae gravidarum, and the Perineal Trauma Grading Scale. Results indicated that 35% of mothers had moderate striae and 45% experienced Grade 1 perineal trauma, with a weak positive correlation (r = 0.621) observed between striae severity and perineal trauma. Religion and socio-economic status showed significant associations with perineal trauma (p < 0.05), while birth weight was significantly associated with striae gravidarum; other demographic variables were not significant. The findings suggest that striae gravidarum could serve as a simple, non-invasive clinical indicator for identifying women at higher risk of perineal trauma, advocating for its inclusion in routine antenatal assessments to facilitate preventive interventions and improve maternal outcomes.